Implementasi Sistem Verifikasi Wajah Untuk Mengatasi Penyalahgunaan Akun Driver Gojek - Muhammad Salman Alfarisi (Scholar Center, 2021)
Illegalnarcotics has spread to all levels of society. Many people admit that the circulation and abuse of narcotics is a very dangerous threat to the younger generation. The purpose of this research is to study and analyze how the application of rehabilitationin addiction healing for drug addicts, given the difficulty of victims or drug users to be separated from drug dependence individually. Drug users or addicts on the one hand are perpetrators of criminal acts, but on the other hand are victims (crime without victims). Rehabilitation of drug addicts is a form of social protection that integrates drug addicts into social order so that they no longer use drugs.The method used in this researchis pure legal research (normative). The results of this study are that medical rehabilitation and social rehabilitationboth partially and collectively have a positive effect on victims of narcotics abuse.